Management Strategies in Optimizing Tax Compliance: Exploring the Influence of E-Filing, Account Representative, and Taxpayer Knowledge - Artika, Dini; Aisyah, Siti (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research aims to determine the influence of e-filing, account representative role, and taxpayer knowledge on tax compliance at the East Medan Primary Tax Office. The research method employed is quantitative, and data were collected through a questionnaire. The population consists of the total number of taxpayers at the East Medan Primary Tax Office, with a sample size of 100 respondents. Data processing utilized SPSS Version 25 software, involving descriptive analysis, multiple regression analysis, hypothesis testing, and determination coefficient. Partial test results indicate that, e-filing does not have a significant influence on tax compliance. Meanwhile, Account Representative Role partially has a significant influence on tax compliance. Lastly, taxpayer knowledge does not have a significant influence on tax compliance. Simultaneous test results show that, collectively, the e-filing, Account Representative Role, and taxpayer knowledge influence tax compliance at the East Medan Primary Tax Office.